APRI index changes after 4 weeks treatment of Pentoxifylline in Chronic Hepatitis B - Zulfan, Zulfan; Hakim Zain, Lukman (Jurnal Kedokteran YARSI, 2008)
Nowadays studies have shown that liver fibrosis is a reversible process. Theraupetic target on hepatic stellate cell (HSC) through inhibition of fibrotic signaling transduction is one of the way to treat liver fibrosis (e.g. pentoxifylline). APRI index, one of the indirect marker of liver fibrosis, had shown significant correlation (Spearman correlation y = 0.7) with liver fibrosis degree in hepatitis B and C. This study was aimed to evaluate the effect of pentoxifylline treatment in 4 weeks for liver fibrosis measured by APRI index. We conducted clinical trial on eleven chronic hepatitis B patients from Adam Malik Hospital Medan, with positive HBsAg at least 6 months after follow up. They were treated with pentoxifylline for 4 weeks. Before and after treatment, APRI index was measured. The result showed a decrease of ALT (64.64+49.61 vs 50.64+26.13;p=0.28), but AST and APRI index increased (91.82+100.16 vs 97.91+146.75; p=0.79) and (1.17+1.07 vs 1.31+1.84; p=0.96) respectively. It was concluded that the effect of pentoxifylline as antifibrotic in the liver measured by APRI index was not proven. It was shown that APRI index increased after 4 weeks treatment of pentoxifylline.